Ancient duplications and functional divergence in the interferon regulatory factors of vertebrates provide insights into the evolution of vertebrate immune systems. (April 2018) - Du, Kang; Zhong, Zaixuan; Fang, Chengchi; Dai, Wei; Shen, Yanjun; Gan, Xiaoni; He, Shunping
Abstract: Interferon regulatory factors (IRFs) were first discovered as transcription factors that regulate the transcription of human interferon (IFN)-β. Increasing evidence shows that they might be important players involved in Adaptive immune system (AIS) evolution. Although numbers of IRFs have been identified in chordates, the evolutionary history and functional diversity of this gene family during the early evolution of vertebrates have remained obscure. Using IRF HMM profile and HMMER searches, we identified 148 IRFs in 11 vertebrates and 4 protochordates. For them, we reconstructed the phylogenetic relationships, determined the synteny conservation, investigated the profile of natural selection, and analyzed the expression patterns in four "living fossil" vertebrates: lamprey, elephant shark, coelacanth and bichir. The results from phylogeny and synteny analysis imply that vertebrate IRFs evolved from three predecessors, instead of four as suggested in a previous study, as results from an ancient duplication followed by special expansions and lost during the vertebrate evolution. The profile of natural selection and expression reveals functional dynamics during the process. Together, they suggest that the 2nd whole-genome duplication (2WGD) provided raw materials for innovation in the IRF family, and that the birth of type-I IFN might be an important factor inducing the establishment of IRF-mediated immune networks. As a member involved in the AIS evolution, IRF provide insights into the process and mechanism involved in the complexity and novelties of vertebrate immune systems. Highlights: 148 IRFs were identified in 11 vertebrates and 4 protochordates. Analysis on the phylogeny and synteny suggested that vertebrate IRFs evolved from three predecessors instead of four. Some vertebrate IRFs bear ancient function, thus free the others from the purifying selcetion to evolved new functions.